Social Media as an Instrument of Public Diplomacy in the Digital Era: A Systematic Literature Review - Khusnu Perdani, Mizana; Afandi, Ridwan; Lusa, Sofian; Indra Sensuse, Dana; Wibowo Putro, Prasetyo Adi; Indriasari, Sofianti (Policy & Governance Review, 2024)
The rapid evolution of digital platforms has reshaped the landscape of diplomacy, creating new opportunities for public interactions. Social media has emerged as a pivotal element in the practice of public diplomacy, enabling nations and governmental entities to communicate with a global audience. However, the use of social media carries an underlying challenge in engaging foreign audiences, especially for developing countries, which is rather difficult to get attention from the international community. By utilizing the Preferred Reporting Items for Systematic Review and Meta- Analyses Method (PRISMA), this SLR will investigate the differences and strategies of social media utilization as a prosperous public diplomacy instrument between developing and developed countries. Moreover, the outcomes of this SLR are anticipated to provide methods for best practices in social media analysis and choose a fixed platform for information dissemination according to the public characteristics of each country. Findings indicate that developing countries have not yet utilized social media effectively and require additional strategies to improve its use. Furthermore, they still emphasize solving specific concerns, especially in politic area, while developed countries mostly focused in shaping public perception for nation branding. The results also suggest that Twitter is the predominant platform for conducting content analysis in social media. The study highlights the importance of implementing effective strategies and policy actions to address the challenges and optimize the positive impact of digital platforms in promoting international relations.